Contested Terrains: Journalists' emergent and official memories of the struggle for democracy in Nigeria (2013)
Studies of collective memories have focused on large-scale armed struggles and natural disaster ignoring, to a large extent, collective memories of unarmed resistance and civil uprisings. In the process, little is known about the nature and development of collective memories of such uprisings. As an attempt to address this gap, the study focused on collective memories of the struggle for democracy in Nigeria, an unarmed uprising that resulted in the arrests, incarceration, torture and even death of many citizens and journalists. From textual analysis of sixteen speeches of President Obasanjo given over a period of eight years; analysis of essays written by 200 college students on their memories of the struggle for democracy, and analysis of interviews with the militant journalist who were in the forefront of the struggle for democracy, the paper identified convergences and divergences in the official, journalists’ and emergent memories of the struggle for democracy. Whereas the three collective memories agreed that the struggle was a bitter and painful one, official memories differ from journalists’ and emergent memories on the heroes victims and villains of the struggle. Official memories also differ from others on the use to which the memories of the struggle should be put: while the official position is that the memories of the struggle should be forgotten and efforts devoted to nation building, others insist that the past should be properly remembered with blames and praises given to whomever they are due. The paper highlighted the memory contest that ensued between governments on the one hand, and journalists and young citizens on the other. The paper concluded that memories of unarmed resistance and civil uprising can be as much contentious, politicized and deployed as a weapon as those of armed large-scale conflicts. There was a strong suggestion that emergent memories of the struggle are being influenced by journalists’ memories